A new sphenodontian (Diapsida: Lepidosauria) from the Upper Triassic (Norian) of Germany and its implications for the mode of sphenodontian evolution - Lisa S. Freisem; Johannes Müller; Hans-Dieter Sues; Gabriela Sobral (BMC Ecology and Evolution, 2024)
Abstract The Arnstadt Formation of Saxony-Anhalt, Germany has yielded some of Germany’s most substantial finds of Late Triassic tetrapods, including the sauropodomorph Plateosaurus and the stem-turtle Proganochelys quenstedti. Here, we describe an almost complete skull of a new sphenodontian taxon from this formation (Norian, 227–208 Ma), making it the oldest known articulated sphenodontian skull from Europe and one of the oldest in the world. The material is represented by the dermal skull roof and by the complete maxilla and temporal region, as well as parts of the palate, braincase, and lower jaw. A phylogenetic assessment recovers it as a basal sphenodontian closely related to Planocephalosaurus robinsonae and to Eusphenodontia, making it the earliest-diverging sphenodontian known with an articulated skull. Its cranial anatomy is generally similar to the well-known Diphydontosaurus avonis from the Rhaetian of England, showing that this successful phenotype was already established in the clade around 10 myr earlier than assumed. An analysis of evolutionary change rates recovers high rates of evolution in basal sphenodontians, with decreasing rates throughout the evolution of the group. However, contrary to previous studies, reversals in this trend were identified, indicating additional peaks of evolutionary change. These results improve our understanding of the early sphenodontian diversity in Europe, providing critical information on evolutionary trends throughout the history of the clade and sparking renewed interest in its evolution.